A Comprehensive Review and Update on Cannabis Hyperemesis Syndrome - Priyadarshini Loganathan; Mahesh Gajendran; Hemant Goyal (Pharmaceuticals)
Cannabis, derived from Cannabis sativa plants, is a prevalent illicit substance in the United States, containing over 400 chemicals, including 100 cannabinoids, each affecting the body’s organs differently upon ingestion. Cannabis hyperemesis syndrome (CHS) is a gut–brain axis disorder characterized by recurring nausea and vomiting intensified by excessive cannabis consumption. CHS often goes undiagnosed due to inconsistent criteria, subjective symptoms, and similarity to cyclical vomiting syndrome (CVS). Understanding the endocannabinoid system (ECS) and its dual response (pro-emetic at higher doses and anti-emetic at lower doses) is crucial in the pathophysiology of CHS. Recent research noted that type 1 cannabinoid receptors in the intestinal nerve plexus exhibit an inhibitory effect on gastrointestinal motility. At the same time, the thermoregulatory function of endocannabinoids might explain compulsive hot bathing in CHS patients. The prevalence of cannabis CHS is expected to rise as legal restrictions on its recreational use decrease in several states. Education and awareness are vital in diagnosing and treating CHS as its prevalence increases. This comprehensive review explores the ECS’s involvement, CHS management approaches, and knowledge gaps to enhance understanding of this syndrome.